Expression of protease activated receptor-2 (PAR-2) in central airways of smokers and non-smokers. Issue 2 (1st February 2002) - Miotto, D; Hollenberg, M D; Bunnett, N W; Papi, A; Braccioni, F; Boschetto, P; Rea, F; Zuin, A; Geppetti, P; Saetta, M; Maestrelli, P; Fabbri, L M; et al.
Abstract : Background: Protease activated receptor-2 (PAR-2) is a transmembrane G protein coupled receptor preferentially activated by trypsin and tryptase. The protease activated receptors play an important role in most components of injury responses including cell proliferation, migration, matrix remodelling, and inflammation. Cigarette smoking causes an inflammatory process in the central airways, peripheral airways, lung parenchyma, and adventitia of pulmonary arteries. Methods: To quantify the expression of PAR-2 in the central airways of smokers and non-smokers, surgical specimens obtained from 30 subjects undergoing lung resection for localised pulmonary lesions (24 with a history of cigarette smoking and six non-smoking control subjects) were examined. Central airways were immunostained with an antiserum specific for PAR-2 and PAR-2 expression was quantified using light microscopy and image analysis. Results: PAR-2 expression was found in bronchial smooth muscle, epithelium, glands, and in the endothelium and smooth muscle of bronchial vessels. PAR-2 expression was similar in the central airways of smokers and non-smokers. When smokers were divided according to the presence of symptoms of chronic bronchitis and chronic airflow limitation, PAR-2 expression was increased in smooth muscle (median 3.8 (interquartile range 2.9–5.8) and 1.4 (1.07–3.4) respectively); glands (33.3 (18.2–43.8) and 16.2 (11.5–22.2), respectively); and bronchial vessels (54.2 (48.7–56.8) and 40.0 (36–40.4), respectively) of smokers with symptoms of chronic bronchitis with normal lung function compared with smokers with chronic airflow limitation (COPD), but the increase was statistically significant (p<0.005) only for bronchial vessels. Conclusions: PAR-2 is present in bronchial smooth muscle, glands, and bronchial vessels of both smokers and non-smokers. An increased expression of PAR-2 was found in bronchial vessels of patients with bronchitis compared with those with COPD.